Digital Teaching Materials using Comprehensive Mathematics Instruction Model for Interactive Mathematics Learning - Delima, Nita; Jaja, Jaja; Kusuma, Dianne Amor (Jurnal Pendidikan MIPA, 2022)
The Ministry of Education and Culture found that the Covid-19 pandemic had caused a significant literacy and numeracy learning loss. The comprehensive mathematics instruction (CMI) model has a pedagogical prescription that is proven to be effective in improving students' mathematical thinking skills. This model can be developed into a digital teaching material that can support interactive learning. This study aims to build digital teaching materials using the CMI model that can support interactive mathematics learning. The research method used is research and development (R & D). The results of this study are in the form of a product named CMI Agent which is the result of the transformation of the CMI model teaching materials into LMS-based digital technology with interactive designs. Based on the studies that have been carried out, it is concluded that CMI Agent can support interactive mathematics learning. Keywords: comprehensive mathematics instruction, teaching materials, research and development. DOI: http://dx.doi.org/10.23960/jpmipa/v23i4.pp1777-1789